2018
DOI: 10.30958/ajt.5-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Perceptions of Adolescents’ Influence on the Purchase Decisions of Family Vacations

Abstract: The adolescent is considered an active element in family purchases, especially in the purchasing decision phase. However, services for family use have been neglected. Therefore, the main objective of this research is tostudy the adolescent's influence on purchase decisions of family vacations. In the empirical phase, several secondary schools were contacted in four main districts througha convenience sample. During this stage, 2,800 questionnaires were delivered in classrooms during May 2016. The adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Adolescents tend to be most knowledgeable and interested in technological products, which will lead them to more influence attempts (Foxman and Tansuhaj 1988). Baía (2018) found that adolescents actually revealed a relevant participation on decisions when their knowledge is higher. Thus, the service knowledge should lead to greater adolescents' influence attempts and more parental receptiveness (Chitakunye 2012, Belch et al 2005, Shah & Mittal 1997, Beatty &Talpade 1994.…”
Section: Product Knowledgementioning
confidence: 91%
See 1 more Smart Citation
“…Adolescents tend to be most knowledgeable and interested in technological products, which will lead them to more influence attempts (Foxman and Tansuhaj 1988). Baía (2018) found that adolescents actually revealed a relevant participation on decisions when their knowledge is higher. Thus, the service knowledge should lead to greater adolescents' influence attempts and more parental receptiveness (Chitakunye 2012, Belch et al 2005, Shah & Mittal 1997, Beatty &Talpade 1994.…”
Section: Product Knowledgementioning
confidence: 91%
“…Past research has shown that adolescents'role on family purchase decisions varying by product, decision stage, adolescent, parental, and family characteristics (Aleti et al 2015 This study examines influence of the national cultural individualism-collectivism and power distance constructs, and consumer socialization effects on adolescent's influence on family purchase decision, considering one technological product: computer for family use, as a relevant issue in family consumption (Barber 2013,Akinyele 2010,Neulinger&Zsoter 2014, Kaur & Singh 2006,Commuri& Gentry 2000. This research presents a holistic approach to adolescent influence, also considering the roleof product knowledge on his/her influence, and the influence of demographic variables such as householdincome and adolescent's gender (Baía 2018, Ali et al 2015. This paper also explores the role of television and internet as antecedents ofadolescent's consumer socialization and its effects on his purchase influence.…”
Section: Introductionmentioning
confidence: 99%
“…Western Europe countries traditionally hold a low power distance (Hofstede 1993). This means that in those countries, parents value adolescents' obedience when compared to parents living in a higher power distance culture (Baía 2018). Thus, parents living in a higher power distance culture are more likely to encourage and be more open to adolescents' influence on family decisions (Shergill et al, 2013).…”
Section: Cultural Dimensions (Power Distance)mentioning
confidence: 99%
“…Considering products where adolescents are primary users, like breakfast cereals, clothes, music, generally, adolescents have autonomy to decide (Ishaque&Tufail 2014, Kaur & Singh 2006, Beatty &Talpade 1994, or in certain products like groceries (Baía 2018, Ashraf & Khan 2016,Chikweche et al 2012, Chitakunye 2012. However, there's a need to deep in the research for those type of products, specially trying to know more about the effects of culture and consumer socialization of adolescents' attempts to influence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation